The inactive X chromosome accumulates widespread epigenetic variability with age - Liu, Yunfeng; Sinke, Lucy; Jonkman, Thomas H.; Slieker, Roderick C.; van Zwet, Erik W.; Daxinger, Lucia; Heijmans, Bastiaan T. (Clinical epigenetics, 2023)
Background Loss of epigenetic control is a hallmark of aging. Among the most prominent roles of epigenetic mechanisms is the inactivation of one of two copies of the X chromosome in females through DNA methylation. Hence, age-related disruption of X-chromosome inactivation (XCI) may contribute to the aging process in women. Methods We analyzed 9,777 CpGs on the X chromosome in whole blood samples from 2343 females and 1688 males (Illumina 450k methylation array) and replicated findings in duplicate using one whole blood and one purified monocyte data set (in total, 991/924 females/males). We used double generalized linear models to detect age-related differentially methylated CpGs (aDMCs), whose mean methylation level differs with age, and age-related variably methylated CpGs (aVMCs), whose methylation level becomes more variable with age. Results In females, aDMCs were relatively uncommon ( n = 33) and preferentially occurred in regions known to escape XCI. In contrast, many CpGs ( n = 987) were found to display an increased variance with age (aVMCs). Of note, the replication rate of aVMCs was also high in purified monocytes (94%), indicating an independence of cell composition. aVMCs accumulated in CpG islands and regions subject to XCI suggesting that they stemmed from the inactive X. In males, carrying an active copy of the X chromosome only, aDMCs ( n = 316) were primarily driven by cell composition, while aVMCs replicated well (95%) but were infrequent ( n = 37). Conclusions Our results imply that age-related DNA methylation differences at the inactive X chromosome are dominated by the accumulation of variability.